Estetyczne transpozycje końca imperium. La Chute de l’URSS: une fin d’ empire, red. Anne-Marie Monluçon, Anna Saignes et Agathe Salha, „Recherches & Travaux” 80/2012, Ellug, Grenoble 2012, 189 ss. - Karwowska, Marzena (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
In 2012, specialists in the field of literature from the Stendhal University (Grenoble, France) published a volume entitled: The fall of the Soviet Union: the End of the Empire (Ellug press). International and interdisciplinary team of humanists (including Polish researchers: Aleksander Fiut, Bogusław Bakuła and Tadeusz Szczepański), working under Anne-Marie Monluçon, Anna Saignes and Agathe Salha, investigated the subject of artistic representation of the fall of the Soviet Empire in literature and visual arts. Articles presented in the volume are an interesting example of the reception of Slavic and Polish literature in France.